Healthcare-associated infections in adult Intensive Care Units (ICUs): An integrative review (Research, Society and Development, 2024)
Healthcare-Associated Infections (HAIs) are frequent adverse events, especially in intensive care units (ICUs), associated with increased morbidity, mortality, and hospital costs. This integrative review aimed to examine the scientific production on HAIs in adult ICUs over the past five years, as well as to identify the main associated factors and prevention strategies. Data were collected from Virtual Health Library (BVS) between 2018 and 2023, and the publications were analyzed based on the PRISMA methodology. The final sample consisted of 10 articles, which identified ventilator-associated pneumonia, urinary tract infections, and bloodstream infections as the main HAIs. The study also highlighted the influence of hospital infrastructure, environmental contamination, patient characteristics with HAIs, the implementation of preventive bundles, and behavioral aspects such as adherence to hand hygiene and nursing professionals' perceptions of these infections. It was concluded that continuous education is essential for successful HAI prevention, with the commitment of healthcare staff, especially the nursing team, to the effective implementation of protocols and bundles being fundamental for reducing risks and adverse events, reaffirming the central role of nursing in care.